1,583 Students Graduate from UTT - Cuffy, David (Guardian)
At the 2012 Presentation of Graduates of the University of Trinidad and Tobago (UTT), five well-known cultural and entertainment personalities were among the students presented with the first time Master of Arts in Carnival Studies.
Keywords: Culture. -- Study and teaching -- Trinidad and Tobago; Steel band music -- Instruction and study -- Trinidad and Tobago; Carnival -- Trinidad and Tobago